1995
DOI: 10.1111/j.1432-1033.1995.0563d.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Half‐Life in the Circulation of a Chemical Conjugate Between a Pro‐Urokinase Derivative and Human Serum Albumin

Abstract: Pro‐urokinase is a natural plasminogen activator that displays a clot‐lysis activity through a fibrin‐dependent mechanism. It seems to be a promising agent for the treatment of coronary thrombosis. Like tissue‐type plasminogen activator and two‐chain urokinase‐type plasminogen activator, pro‐urokinase has a very short half‐life in circulation. It has been described that conjugation of serum albumin with pro‐urokinase in plasma may occur that could protect this protein from degradation. In this study we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…Although the liver uptake of deltal25-rscu-PA was completely blocked by GST-RAP still a relatively rapid clearance from the circulation was observed, probably due to extra-hepatic uptake of this rather small molecule (31.8 kDa). The latter is in line with Breton et al (53) who showed that a conjugate of deltal25-rscu-PA with serum albumin injected in monkeys shows a dramatic increase in serum half-life compared to deltal25-rscu-PA alone. It is thought that the conjugation with albumin protects the deltal25-rscu-PA molecule probably for extravascularization.…”
Section: Discussionsupporting
confidence: 90%
“…Although the liver uptake of deltal25-rscu-PA was completely blocked by GST-RAP still a relatively rapid clearance from the circulation was observed, probably due to extra-hepatic uptake of this rather small molecule (31.8 kDa). The latter is in line with Breton et al (53) who showed that a conjugate of deltal25-rscu-PA with serum albumin injected in monkeys shows a dramatic increase in serum half-life compared to deltal25-rscu-PA alone. It is thought that the conjugation with albumin protects the deltal25-rscu-PA molecule probably for extravascularization.…”
Section: Discussionsupporting
confidence: 90%
“…8 The circulation half-lives of the drugs have been reported to dramatically increase when the drug is conjugated with albumin. 9 Increasing the circulation half-life of the formulation by reducing its uptake by the reticuloendothelial system has been shown to improve the targeting efficiency of the formulation to the arthritic paws of rats. 10 There are several reports on the use of long circulating liposomes to target the drugs to the arthritic joints.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous administration of the drugs coupled with Albumin has been reported to improve the targeting efficiency of the drug to arthritic regions [13]. The circulation halflives of the drugs have been reported to dramatically increase when the drug is conjugated with albümin [14]. Increasing the circulation half-life of the formulation by reducing its uptake by the reticuloendothelial system has been shown to improve the targeting efficiency of the formulation to the arthritic paws of rats [15].…”
Section: Introductionmentioning
confidence: 99%